Design of circular-shaped microstrip patch antenna for 5G applications - Mohammed Mahdi Salih Altufaili; Ameer Najm Najaf; Zainab Sabah Idan (Universitas Ahmad Dahlan, 2022)
Using circular geometry has a great influence on many fields of science and engineering, one of which is antenna. Communication systems were oriented towards fifth generation (5G) because of large- bandwidth systems, compact requirements, high-data rates. In this research, a design and simulation are made to a microstrip circular patch antenna. The patch has two circles a compact structure of the first circle radius is 2.5 mm and second circle radius is 1 mm with thickness 0.35 mm. The proposed antenna has three resonant frequencies 41.08 GHz with a return loss of -12.4 dB, 47.4 at -18.86 dB and 54.4 at return loss -24.3 dB. The bandwidths are 150 MHz, 222 MHz and 219 MHz, the gains of three resonant frequencies are 6.16 dB, 9.89 dB and 5.54 dB, with efficiency of 98%. A technique of inset feed transmission line was utilized to match the fifty Ω microstrip feedline and the radiating patch. Based upon the proposed design, a Roger RT Duroid 5880 substrate that possesses loss tangent of 0.0009 with a height of 0.5 mm and a dielectric constant of 2.2 is employed. A computational process is conducted and analyzed by the use of computer simulation technology microwave studio.